Creativity and paternalistic leadership in a developing country's restaurants: The role of job embeddedness and career stage. (15th January 2021) - Khorakian, Alireza; Baregheh, Anahita; Eslami, Ghasem; Yazdani, Narjes; Maharati, Yaghoob; Jahangir, Mostafa
Abstract: This study investigates the relationship between paternalistic leadership and employee creativity in the tourism and hospitality industry, considering the mediating role of job embeddedness and the moderating role of career stage based on Social Exchange Theory and Conservation of Resources Theory . A paired survey questionnaire was developed and distributed to evaluate the research variables targeting managers and chefs of restaurants in a developing country. To analyze the data, structural equation modeling has been used. Findings demonstrate that job embeddedness has a positive effect on creativity as well as a mediating role between moral and benevolence leadership and creativity. Moreover, employees' career stage is positively linked to job embeddedness and creativity. This study contributes to the existing literature by studying the role that job embeddedness and career path play on employee creativity. Thus, reflecting on how the tourism and hospitality industry can be more innovative, considering the specific sociocultural features given that the study is conducted in a tourist city in a developing country.